In vivo solid-phase microextraction sampling combined with metabolomics and toxicological studies for the non-lethal monitoring of the exposome in fish tissue. (June 2019) - Roszkowska, Anna; Yu, Miao; Bessonneau, Vincent; Ings, Jennifer; McMaster, Mark; Smith, Richard; Bragg, Leslie; Servos, Mark; Pawliszyn, Janusz
Abstract: Various environmental studies have employed the biomonitoring of fish in their aquatic ecosystems in order to identify potential metabolic responses to the exposome. In this study, we applied in vivo solid-phase microextraction (SPME) to perform non-lethal sampling on the muscle tissue of living fish to extract toxicants and various endogenous metabolites. Sixty white suckers ( Catastomus commersonii) were sampled from sites upstream, adjacent, and downstream from the oil sands development region of the Athabasca River (Alberta, Canada) in order to track their biochemical responses to potential contaminants. In vivo SPME sampling facilitated the extraction of a wide range of endogenous metabolites, mainly related to lipid metabolism. The obtained results revealed significant changes in the levels of numerous metabolites, including eicosanoids, linoleic acids, and fat-soluble vitamins, in fish sampled in different areas of the river, thus demonstrating SPME's applicability for the direct monitoring of exposure to different environmental toxicants. In addition, several classes of toxins, including petroleum-related compounds, that can cause serious physiological impairment were tentatively identified in the extracts. In vivo SPME, combined with the analysis of contaminants and endogenous metabolites, provided important information about the exposome; as such, this approach represents a potentially powerful and non-lethal tool for identifying the mechanisms that produce altered metabolic pathways in response to the mixtures of different environmental pollutants. Graphical abstract: Image 1 Highlights: A non-lethal method for in vivo sampling of fish muscle tissue was applied. The SPME blade was directly inserted in the tissue for low-invasive extraction. SPME provides accurate information about the composition of toxicants and endogenous metabolites in the living system. In vivo SPME facilitates monitoring of the metabolic alterations in fish exposed to environmental changes.